The Cytoarchitecture of the Tectal-Related Pallium of Squirrelfish, Holocentrus sp. - Demski, Leo S.; Beaver, Joel A. (Frontiers in Neuroanatomy, 2022)
The squirrelfishes, which live in visually complex coral reefs, have exceptionally large eyes and a special dual-system-“day and night vision” retina. They also have atypical expansions of brain areas involved in processing this visual information. The midbrain optic lobes or tectum sends information to two enlarged dorsal pallial regions. The latter include a superficial dorsal/lateral “cortex-like area” of small to medium-size cells (area dorsalis telencephali pars lateralis) which controls an underlying dorsocentral region of relatively large cells (area dorsalis telencephali pars centralis) which in turn reconnects with the tectum. Additionally, the cerebellum is also involved in this “loop”. The hypertrophied dorsal pallium most likely exerts major influences on a variety of visually-related sensorimotor systems. This research aimed at better establishing the cytoarchitecture and internal connections of the tectal-related pallium. Nissl and rapid Golgi staining; biotinylated dextran amine tracing and cell-filling; and electron microscopy were used to establish a “working model” of the pallial “visual system”. For in situ gross observation of the pallial areas and plotting of the study sites, a mini-atlas of transverse and horizontal sections was constructed. Besides better documenting the known elements, two novel cell-types were found. Comparisons of the present results with similar systems in other species are considered as such may relate diversity of the structures with differences in fish behavior and ecology.